Development and Validation of a Telerehabilitation Protocol for Shoulder Dysfunction: Kinematic Analysis and Functional Recovery Metrics - Kaushik, Leeladhar; Singh, Prashant; Shukla, Parshuram (Journal of Contemporary Medical Practice, 2025)
The shoulder emphasizes the synchronized movement of four joints: glenohumeral, scapulothoracic, sternoclavicular and acromioclavicular. As the humerus moves into elevation, movement must occur at all four joints. This joint movement has been described as the joint arthrokinematics, or the intricate movement of the joint surfaces. Normal arthrokinematic movements occur only in the presence of normal periarticular connective tissue, extensibility, and integrity and muscle function. A stiff shoulder has limited capsular flexibility and altered muscle function. In order to re - establish harmonious movement within the shoulder complex the therapist must rehabilitate the connective tissue by restoring its extensibility, and restore normal balance of muscles. The deltoid muscle is often forgotten when it comes to the evaluation and planning of treatment in shoulder conditions. Shoulder dysfunction, rotator cuff tendinopathy, and frozen shoulder are the conditions that affect functioning in major cases. This study involved an exploration of possible causes of dysfunction, especially pain and overhead activities. The patient presented with acute pain and decreased shoulder function. A suitable shoulder rehabilitation program was designed keeping the deltoid muscle denervation into consideration. The shoulder pain, range of motion, strength, and function were evaluated on day one, followed by weekly assessment for seven weeks. The results were correlated and explored to identify the involvement of the deltoid muscle. There was a clinically significant improvement observed in the patients' function. Hence, the study hypothesized that along with scapular stabilization, it is important to consider deltoid equally during the assessment and treatment plan in shoulder rehabilitation program.